Using Loss Aversion to Motivate Exercise; a Longitudinal Research - Yuliana, Desi (Jurnal Akuntansi, Manajemen dan Ekonomi, 2023)
The modern lifestyles have resulted in physical inactivity and sedentary behavior which cause a lot of chronic illnesses. The benefits of exercising are becoming widespread knowledge but it is still challenging to change our behavior to a healthier one. The prior works in the literature in the field of behavior change are divided into two major groups: positive and negative reinforcement. Positive reinforcements’ work are more popular in encouraging exercise but negative reinforcements are more focused on other behavior change fields such as quit smoking therapy and children’s behavior modification. Our study aims to apply negative reinforcements for promoting exercise habit. In our experiments, we observed the behavior of 10 participants to perform physical activities such as running, jogging, and cycling, under the negative reinforcements’ influence. We collected an initial deposit from the treatment groups and a portion of the deposit was returned per exercise only when they meet our goal for the week. The experiment lasted for 3 weeks with increasing goals every week. We found that the treatment groups performed better in attaining the weekly goals relative to the control group with the negative intervention having a significant effect on motivating users to exercise.